2006
DOI: 10.1007/s11104-006-9015-5
|View full text |Cite
|
Sign up to set email alerts
|

Alleviation of salt stress in Lotus glaber by Glomus intraradices

Abstract: Lotus glaber is a glycophytic, perennial legume from Europe that occurs widely in saline habitats. We evaluated the effect of mycorrhizal fungus colonization on the response to salt stress of two genotypes of L. glaber differing in their tolerance to salinity. The experiment consisted of a randomized block design with two factors: (1) mycorrhizal fungus treatments (with or without AM fungus) and (2) two salinity levels of 0 and 200 mM NaCl. Our results indicated that Glomus intraradices established a more effi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
50
0
4

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(72 citation statements)
references
References 31 publications
(29 reference statements)
18
50
0
4
Order By: Relevance
“…Inoculation with AMF improves growth of plants under a variety of salt stress conditions (Al-Karaki et al 2001;Giri et al 2003;Sannazzaro et al 2006). We have observed the same for shoot and root dry weights of K. virginica inoculated with AMF and/or Ms at all salinity levels.…”
Section: Effect Of Inoculation On Plant Growth Under Salt Stresssupporting
confidence: 71%
See 1 more Smart Citation
“…Inoculation with AMF improves growth of plants under a variety of salt stress conditions (Al-Karaki et al 2001;Giri et al 2003;Sannazzaro et al 2006). We have observed the same for shoot and root dry weights of K. virginica inoculated with AMF and/or Ms at all salinity levels.…”
Section: Effect Of Inoculation On Plant Growth Under Salt Stresssupporting
confidence: 71%
“…Studies have showed that AMF widely occur in salt environments (Rozema et al 1986;Wang and Liu 2001) and can improve growth and productivity in both glycophytes and halophytes under salt stress (Asghari et al 2005;Sannazzaro et al 2006;Giri et al 2007). Rodriguez and Fraga (1999) suggested that the inoculated rhizobacteria could release P ions from insoluble P sources and the released P was taken up by the external arbuscular mycorrhizal mycelium because the rhizobacteria cannot transfer P to roots.…”
Section: Introductionmentioning
confidence: 99%
“…But mycorrhizal inoculation can alleviate this problem to some extent and in our study, at each salinity level, significantly higher chlorophyll content was detected in leaves of G. max and C. tetragonoloba plants as compared with respective nonmycorrhizal plants. Thus, Gm and Gf association (individually and in combination) enhanced the photosynthetic ability of G. max and C. tetragonoloba under salinity stress, which is in agreement with earlier report (Sonnazzaro et al, 2006). Data from present study indicated that, regardless of host plant, maximum chlorophyll accumulation occurred by AM fungi in coassociation as compared to their individual association.…”
Section: Discussionsupporting
confidence: 92%
“…Studies on abiotic stress in L. tenuis have been focused principally on NaCl tolerance (Sánchez et al 2005;Sannazzaro et al 2006Sannazzaro et al , 2007Echeverria et al 2008;Uchiya et al, 2016), whereas less studies has addressed its tolerance level to alkaline and mixed salt-alkaline stresses. Alkaline salts have a more severe effect on plant growth than neutral salts.…”
Section: Abiotic Stressesmentioning
confidence: 99%